2014
DOI: 10.1093/nar/gku189
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Z-DNA binding mode of a PKR-like protein kinase containing a Z-DNA binding domain (PKZ)

Abstract: Double-stranded ribonucleic acid-activated protein kinase (PKR) downregulates translation as a defense mechanism against viral infection. In fish species, PKZ, a PKR-like protein kinase containing left-handed deoxyribonucleic acid (Z-DNA) binding domains, performs a similar role in the antiviral response. To understand the role of PKZ in Z-DNA recognition and innate immune response, we performed structural and functional studies of the Z-DNA binding domain (Zα) of PKZ from Carassius auratus (caZαPKZ). The 1.7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 51 publications
3
56
0
Order By: Relevance
“…PKZ, which instead of dsRNA-binding domains has two Z␣ domains (11), was shown to phosphorylate eukaryotic initiation factor 2␣ similarly to PKR in response to CpG DNA, but not to poly(IC), a classic dsRNA activator of PKR (13). Previously, we and others solved the crystal structures of the PKZ-Z␣ domain (7,14) and clarified the details of the interaction of PKZ-Z␣ with Z-DNA.…”
mentioning
confidence: 99%
“…PKZ, which instead of dsRNA-binding domains has two Z␣ domains (11), was shown to phosphorylate eukaryotic initiation factor 2␣ similarly to PKR in response to CpG DNA, but not to poly(IC), a classic dsRNA activator of PKR (13). Previously, we and others solved the crystal structures of the PKZ-Z␣ domain (7,14) and clarified the details of the interaction of PKZ-Z␣ with Z-DNA.…”
mentioning
confidence: 99%
“…The results indicated that Dcc1 contains three‐winged helix (WH) domains from residues 182–252, 253–317 and 318–380, which we have called WH1, WH2 and WH3, respectively (Fig C). These WH domains show structural homology to the WH domains from PKZ , cullin‐1 and DsrD , with Z‐scores of 5.7, 7.4 and 4.9, respectively (Fig EV1). WH domains are often involved in DNA binding or mediating protein–protein interactions , suggesting possible functions for this structural feature.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] The crystal structures of various ZBPs in complex with 6-base-paired (6-bp) CG-repeat DNA found that the interaction with Z-DNA is mediated by the α3 helix and in the β-hairpin. [4][5][6][7] When the ZBPs produce Z-DNA segments in a genomic DNA, two B-Z junctions at each end of Z-DNA should be formed. A crystal structural study of the Zα domain of human ADAR1 (Zα ADAR1 ) complexed with 15-bp DNA showed that DNA are stabilized at one end in the Z-conformation by Zα ADAR1 proteins, while the other end remains B-DNA.…”
Section: Introductionmentioning
confidence: 99%